Identification of SRAP molecular markers linked to powdery mildew resistance in cucumber - JING Ran; CHEN Xin-juan; ZHU Yu-qiang; ZHANG Peng; ZHANG Yu-qiong; ZHOU Shengjun (浙江大学学报. 农业与生命科学版)
With a F2 population between a resistant parent and susceptible parent, SRAP analysis was carried to develop molecular markers linked to powdery mildew in cucumber. Sixty-two pairs of primer combinations which had stable amplified polymorphic bands between resistant parent and susceptible parent were selected from 437 pairs of SRAP primer combinations. Further analyzing the F2 segregating populations using these primers, one SRAP marker of Me1 /Em9—284 bp linked to the powdery mildew resistance was found, with 9.8 cM genetic distance. The marker can be used for cloning disease-resistant gene and advancing efficiency of disease-resistant breeding on molecular marker assisted selection.